Optimalisasi Fermentasi Gulma sebagai Pupuk Organik Cair Ramah Lingkungan untuk Meningkatkan Pertumbuhan dan Kandungan Nutrien Tanaman Pakan: Optimization of Weed Fermentation as an Eco-Friendly Liquid Organic Fertilizer to Enhance Growth and Nutrient Content of Forage Plants - Insani, Andi Nur; Mariam, Mariam; Sudarsono, Sudarsono; Rustan (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2025)
This study aims to evaluate the effect of fermented weeds as an environmentally friendly liquid organic fertilizer on the growth and proximate composition of superior forage crops, namely biovit elephant grass (RBV), red elephant grass (RGM), and bio-nutrient elephant grass (RBN). Design of the experiment was a completely randomized design in a factorial pattern, with the first factor being three grass varieties and the second factor being four dosages of liquid fertilizer (P0: no fertilization, P1: 30 mL, P2: 40 mL, and P3: 50 mL) with three replications. The tested growth parameters included plant height, chlorophyll content, and proximate analysis consisting of crude protein, crude fiber, and fat content. The results showed that the liquid fertilizer treatment at a dosage of 50 mL had a significant effect on growth and nutrient composition, with red elephant grass (RGM) exhibiting the best (p<0.05) crude protein and fat content. Additionally, higher dosages of liquid fertilizer contributed to a reduction (p<0.05) in crude fiber content. This study concludes that fermented weeds can be used as a liquid organic fertilizer to optimize and enhance the growth and nutritional quality of superior forage crops. Keywords: growth, liquid organic fertilizer, nutrient composition, superior forage crops, weed fermentation